Leer y escribir para aprender historia: secuencias para la enseñanza y el aprendizaje del pensamiento histórico de 7o a 4to medio (Ediciones UC, 1905)
The book 'Reading and writing to learn history' is a proposal for teaching and learning History based on reading and writing practices, and provides a set of theoretical and practical tools that can be adapted to each context. It is a manual that serves both students and classroom teachers of History and Social Sciences as well as teachers of Language, Science and all those interested in the development of academic discourse through the school curriculum. This text presents 10 teaching and learning sequences from 7th grade to 4th grade, whose purpose was to develop historical reading and writing skills in children and young people. The authors of the text have investigated and implemented this model of teaching History in learning sequences (similar to a "work guide") through the development of historical reading and writing in students. It was based on the assumption that learning a discipline is to learn a particular kind of disciplinary language and thought.This is the starting point of this book: to identify the classroom practices of historical reading, reasoning, and writing that offer the best opportunities for the development of the more complex skills of historical thinking and , at the same time, of the curricular objectives of 7th grade to 4th grade of History and Social Sciences.